La mirada mulveyana y el baño de Betsabé en la Baja Edad Media - Walker Vadillo, Mónica Ann (Anales de Historia del Arte, 2010)
In 1975 Laura Mulvey published “Visual Pleasure and Narrative Cinema” and ever since it has been a constant reference in film and artistic studies. Mulvey developed a theory of the male gaze and its relation to the subject of the gaze based on the studies conducted by Sigmund Freud and Jacques Lacan. This article tries to read the iconography of Bathsheba’s bath as it appears in Late Medieval books of hours in mulveian terms. This iconography from the Old Testament is ideal to do such a reading since the gaze is central to the story. Not only is the gaze of King David watching Bathsheba bathing involved here, but also the gaze of the artist that created the image and the gaze of the spectator. Even though the theory applied here is a postmodernist theory, the discourse of the gaze as it was discussed during the Middle Ages will be taken into consideration.